Methanol poisoning: Analysis of a case series in two public hospitals - Venegas-Justiniano, Yanissa (2024)
Objective: To describe the clinical and epidemiological characteristics of patients with methanol poisoning in two public hospitals. Materials and methods: Retrospective case series, 41 medical records of patients admitted to emergency with a diagnosis of methanol intoxication in the period 2018-2022 in two public hospitals in Lima-Peru were reviewed. Patients were from Arzobispo Loayza National Hospital and Hipolito Unanue Hospital. Results: Of the 41 patients, 35 were male, with a mean age of 44.4 years. Nearly 50% were admitted to the intensive care unit (ICU), and 23/41 (56,1%) required hemodialysis. All patients presented severe metabolic acidosis with elevated anion gap. Forty-eight hours after admission, 9/41 (21,9%) patients died. Of those who survived, 23/41 (56,1%) had sequelae: 21 patients developed toxic optic neuropathy and two patients had motor sequelae due to hemorrhagic stroke. Lower pH (6,7 vs. 7,1, p<0,001) and bicarbonate (3 mmol/L vs.4,9 mmol/L, p= 0,004) levels, as well as higher lactate (9,6 mmol/L vs 2,3 mmol/L, p<0,001) and sodium (142,5 mmol/L vs. 138 mmol/L, p<0,036) values were evidenced in the deceased patients compared to those who survived. Conclusion: Methanol poisoning continues to be a condition that leaves sequelae and it may lead to death. Severe metabolic acidosis with an elevated anion gap, associated with respiratory and neurological symptoms are its main manifestations; therapy is based on the administration of ethanol, bicarbonate, and hemodialysis support.